The Global Spread of Microplastics: Contamination in Mussels, Clams, and Crustaceans from World Markets - Tamara Mutić; Jelena Mutić; Miloš Ilić; Vesna Jovanović; Jelena Aćimović; Boban Andjelković; Dragana Stanić-Vucinić; Maria Krishna de Guzman; Mirjana Andjelkovic; Mirjana Turkalj; Tanja Cirkovic Velickovic (Foods)
Analysis of microplastic (MP) occurrence in commercially relevant species is a prerequisite for food risk assessment. Using a standardized methodology, we aimed to investigate MP contamination in point-of-sale clams, mussels, and Crustacea shellfish collected from various markets (Belgium, Croatia, Serbia, and South Korea). An improved digestion protocol yielded ≥ 99.8% digestion efficiency for all species analyzed. In a total of 190 samples analyzed individually by microFTIR, MPs were identified in 43.68% of the samples with less than 1 MP/individual average (0–4 MP/individual, 0–1.35 MPs/g tissue). Significant differences between species were observed when considering samples contaminated with MPs, with Crustacea shellfish having the lowest MPs/g of edible tissue. Polystyrene, polypropylene, and polyethylene were dominant MPs found in clams and mussels, while polyamide, polyethylene terephthalate, and polyvinyl chloride were the most abundant in Crustacea shellfish. Our data do not support the bioaccumulation or biomagnification of MPs with the size of the animal in the shellfish group. MP contamination is more strongly associated with the type of shellfish than with the geographical origin of the market.